Multiproxy quantitative paleoceanographic dataset from late Quaternary marine sediment archives in the western Ross Sea (Antarctica) - Torricella F.; Colizza E.; Cornamusini G.; Del Carlo P.; Giglio F.; Hong J. K.; Khim B. -K.; Kuhn G.; Macri P.; Malinverno E.; Melis R.; Sagnotti L.; et al. (Data in Brief, 2024)
The past ice sheet dynamics and the timing of retreat events in the paleo-record in the Ross Sea is an issue still few understood. In order to contribute to this topic, we provide a multiproxy data from marine sediment archives (cores and box cores) collected in three sites in the Central Basin (Western Ross Sea, Antarctica). Each site recorded different environments, affected by different oceanographic conditions and sedimentary regime. This makes the three investigated sediment cores and box cores unique and useful for comparison with other studied cores collected in the same basin. The data set includes physical (paleomagnetism, grain size and petrography), chemical, micropaleontological (diatom, foraminifera and silicoflagellate assemblages) analyses and cryptotephra characterization increasing the information already reported in literature. The importance of this dataset is related to a multi-disciplinary approach in a site, the Central Basin, few investigated which represents a key area to connect the Southern Ocean and the Ross Sea. (c) 2024 The Authors. Published by Elsevier Inc. This is an open access article under the CC BY-NC license ( http://creativecommons.org/licenses/by-nc/4.0/ )